(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract :This article explores the impact of stacking fault energy (SFE) on induced plasticity, encompassing strain hardening, grain size hardening, solid solution hardening, and precipitation hardening in manganese steel displaying TRIP/TWIP phenomena . It demonstrates how TRIP and TWIP influence the mechanical and sliding wear characteristics of manganese steel, noting that TWIP enhances strength via improved plasticity . The study highlights the significant role of microalloying elements in intermetallic precipitation, which enhances the steel’s hardness and strength, leading to improved sliding wear resistance in both lubricated and unlubricated conditions .